2004
DOI: 10.1016/s0894-1777(03)00107-9
|View full text |Cite
|
Sign up to set email alerts
|

Flow structures and heat transfer characteristics in fan flows with and without delta-wing vortex generators

Abstract: Effects of an external delta-wing vortex generator on the flow and heat transfer characteristics in fan flows and uniform flows were experimentally investigated and compared. A heated plate, installed on the bottom wall of a duct, was used as the heat transfer surface. Three-component mean and fluctuating velocity measurements were conducted using a laser Doppler velocimetry to characterize the flow structures and to obtain the near-wall flow parameters, including the axial mean velocity, axial vorticity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…They also indicated that an optimization should be made for the fin with a winglet in order to improve its performance. Chen and Shu (2004) determined the effects of the delta-wing vortex generator on uniform and fan flows as well as on heat transfer. The effect of the delta wing on heat transfer performance is found to be larger for a uniform flow since the fan flow is already vortical without a delta wing.…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that an optimization should be made for the fin with a winglet in order to improve its performance. Chen and Shu (2004) determined the effects of the delta-wing vortex generator on uniform and fan flows as well as on heat transfer. The effect of the delta wing on heat transfer performance is found to be larger for a uniform flow since the fan flow is already vortical without a delta wing.…”
Section: Introductionmentioning
confidence: 99%
“…In similar studies Tahat et al [5], Tahat et al [6], El-sayed et al [7], Chen and Shu [19], Jubran and Al-Salaymeh [20] etc., reported that the total radiative heat-losses from a similar test surface would be about 0.5% of the total electrical heat-input. Also the base plate and fins were of aluminum; their surfaces being highly polished and so of low emissivity.…”
Section: Calculation Of the Heat Transfer And Friction Factormentioning
confidence: 75%
“…In similar studies, Tahat et al [4], Tahat et al [5], El-sayed et al [11], Chen and Shu [24], Jubran and Al-Salaymeh [25] reported that the total radiative heat loss from a similar test surface would be about 0.5% of the total electrical input. Also the base plate and fins were of aluminum: their surfaces were highly polished and so of low emissivity.…”
Section: Calculation Of the Heat Transfer And Friction Factormentioning
confidence: 83%